2020
DOI: 10.1055/s-0040-1701235
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Complications and Sepsis Following Severe Acute Subdural Hematoma in Patients Who Underwent Craniotomy versus Craniectomy: A Propensity Score Matched Analysis

Abstract: Background The purpose of the study was to evaluate the impact of craniotomy (CO) and decompressive craniectomy (DC) for evacuation of acute subdural hematoma (SDH) on pulmonary complications and sepsis. Methods Study data were obtained from the National Trauma Data Bank (2007–2010). Only patients who met all of the following criteria were included in this analysis: sustained blunt injuries, presented with severe traumatic brain injury, sustained an associated SDH, presented with an initial Glasgow C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Pulmonary complications are well-described in patients with TBI and complications present in patients with TBI and SDH can be even life-threatening. Among 2370 patients with SDH, which included 1852 patients who underwent craniotomy and 518 who underwent DC, there were no significant differences between the two groups regarding acute respiratory distress syndrome, pneumonia, and pulmonary embolism [ 31 ]. A multi-center observational study comparing craniotomy and DC showed that DC was associated with more complications than craniotomy, but the in-hospital mortality odds were similar between the two groups [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary complications are well-described in patients with TBI and complications present in patients with TBI and SDH can be even life-threatening. Among 2370 patients with SDH, which included 1852 patients who underwent craniotomy and 518 who underwent DC, there were no significant differences between the two groups regarding acute respiratory distress syndrome, pneumonia, and pulmonary embolism [ 31 ]. A multi-center observational study comparing craniotomy and DC showed that DC was associated with more complications than craniotomy, but the in-hospital mortality odds were similar between the two groups [ 32 ].…”
Section: Discussionmentioning
confidence: 99%